Stimuli-responsive micro/nanoporous hairy skin for adaptive thermal insulation and infrared camouflage. Issue 12 (22nd October 2020) - Choe, Ayoung; Yeom, Jeonghee; Kwon, Yeju; Lee, Youngoh; Shin, Young-Eun; Kim, Jinyoung; Ko, Hyunhyub
Abstract : A smart hairy skin with hiearchical micro/nanoporous shape memory polymer enables dynamically adaptive thermal insulation. Abstract : Hairs in homeothermic animals have multiple functions essential for survival, such as regulation of body temperature and camouflage, through adaptable reconfiguration in response to external environments. By contrast, humans wear clothes because the human skin is ineffective for thermoregulation and camouflage, but clothes do not exhibit dynamic responsiveness. In this work, we demonstrate a smart reconfigurable hairy skin based on a hair-patterned shape memory polymer (SMP) containing hierarchical porous micro/nanostructures, which has unique functions of dynamically responsive thermal insulation and camouflage from infrared surveillance. The hairy SMP exhibits high thermal insulation due to the long tortuous path of thermal transport in the micro/nanopores. The programmable shape of the hairy SMP enables the reversible reconfiguration of the hair geometry in response to temperature, leading to the dynamic control of thermal insulation by more than 61.4%. As a proof-of-concept, the smart hairy skin can be used as wearable thermal camouflage or thermal encryption films.